Cytochrome P450 2D6 and 3A4 enzyme inhibition by amine stimulants in dietary supplements. Issue 3 (11th September 2015) - Liu, Yitong; Santillo, Michael F.
Abstract : A number of dietary supplements used for weight loss and athletic performance enhancement have been recently shown to contain a variety of stimulants, for which there is a lack of pharmacological and toxicological information. One concern for these emerging compounds is their potential to inhibit metabolic enzymes in the liver such as cytochromes P450 (CYP), which can lead to unexpected interactions among dietary supplements, drugs, and other xenobiotics. In this study, inhibition of human recombinant CYP2D6 and CYP3A4 by 27 amine stimulants associated with dietary supplements and their analogs was evaluated by luminescence assays. The strongest CYP2D6 inhibitors were coclaurine ( IC 50  = 0.14 ± 0.01 μM) and N ‐benzylphenethylamine ( IC 50  = 0.7 ± 0.2 μM), followed by several other relatively strong inhibitors ( IC 50, 2–12 μM) including β‐methylphenethylamine, N, β‐dimethylphenethylamine (phenpromethamine), 1, 3‐dimethylamylamine (DMAA), N, α‐diethylphenethylamine, higenamine (norcoclaurine) and N, N ‐diethylphenethylamine. Only nine compounds inhibited CYP3A4 by 20–55% at 100 μM. Results of this study illustrate that several amine stimulants associated with dietary supplements inhibit CYP2D6 and CYP3A4 in vitro, and these compounds may participate in adverse drug‐dietary supplement interactions in vivo . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A total of 27 amine stimulants found in dietary supplements, as well as chemical analogs that could emerge in future supplements, were tested in vitro for inhibition of cytochromes P450 (CYP) 2D6 and 3A4, two important liver metabolic enzymes. Several compounds were potent CYP2D6 inhibitors, while all were relatively weak CYP3A4 inhibitors. Results of this study showed that several compounds studied were CYP2D6 inhibitors in vitro, which could indicate involvement in potential adverse dietary supplement‐drug interactions in vivo.